Atlas of the potential vegetation of Ethiopia - Friis, Ib.; Sebsebe Demissew; Breugel, Paulo van. (Addis Ababa, Ethiopia : Addis Ababa University Press : Shama Books, 2011)
"A new map of the potential vegetation types of Ethiopia has been produced at the scale of 1:2,000,000. It is published here as an atlas with 29 map plates. The map shows the distribution of twelve potential vegetation types that can be mapped using environmental parameters and GIS methodology. In the accompanying text these vegetation types have been described and further divided into a number of subtypes. The types and subtypes are: (1) Desert and semi-desert scrubland. (2) Acacia-Commiphora woodland and bushland (with the subtypes (2a) Acacia-Commiphora woodland and bushland proper and (2b) Acacia wooded grassland of the Rift Valley). (3) Wooded grassland of the western Gambela region. (4) Combretum-Terminalia woodland and wooded grassland. (5) Dry evergreen Afromontane forest and grassland complex (with the subtypes (5a) Undifferentiated Afromontane forest, (5b) Dry single-dominant Afromontane forest of the Ethiopian highlands, (5c) Afromontane woodland, wooded grassland and grassland, (5d) Transition between Afromontane vegetation and Acacia-Commiphora bushland on the Eastern escarpment). (6) Moist evergreen Afromontane forest (with the subtypes (6a) Primary or mature secondary moist evergreen Afromontane forest, and (6b) Edges of moist evergreen Afromontane forest, bushland, woodland and wooded grassland). (7) Transitional rain forest. (8) Ericaceous belt. (8) Afroalpine belt. (10) Riverine vegetation. (11) Fresh-water lakes, etc. (with the subtypes (11a) Fresh-water lake vegetation (open water) and (11b) Freshwater marshes and swamps, floodplains and lake shore vegetation). (12) Salt lakes, etc. (with the subtypes (12a) Salt lake vegetation (open water) and (12b) Salt pans, saline brackish and intermittent wetlands and salt-lake shore vegetation)"--Synopsis.
Topography, geology, soil and climate of Ethiopia -- Methods : sources and scale of the new vegetation map -- Previous vegetation maps of Ethiopia and their mapping units -- Potential vegetation types in Ethiopia -- Appendix 1: The vegetation types of Ethiopia according to Pichi Sermolli (1957) -- Appendix 2: The vegetation types of Ethiopia according to White (1983) -- Appendix 3: Woody plants in the Flora of Ethiopia and Eritrea, assigned to vegetation types -- Appendix 4: Development of classification system critieria and their implementation in GRASS GIS script for the Atlas of the Potential Vegetation of Ethiopia -- Appendix 5: Officially recognised classification of the ecosystems of Ethiopia.
First published by The Royal Danish Academy of Sciences and Letters, 2010.
Includes bibliographical references (p. 255-[257]) and indexes.
Keywords: Plant communities -- Ethiopia; Vegetation surveys -- Ethiopia; Plants -- Ethiopia; Botany -- Ethiopia; Botany; Plant communities; Plants; Vegetation surveys; Ethiopia